Altered Peroxisome-Proliferator Activated Receptors Expression in Human Endometrial Cancer - Paweł Knapp; Adrian Chabowski; Agnieszka Błachnio-Zabielska; Katarzyna Jarząbek; Sławomir Wołczyński (PPAR Research)
Peroxisome proliferator-activated receptors (PPARs) belong to a family of nuclear hormone receptors acting as transcriptional factors, recently involved also in carcinogenesis. Present study was undertaken to evaluate the presence and subcellular localization of different PPAR isoforms (α, β, γ) in healthy endometrial tissue (n=10) and endometrial carcinoma (FIGO I, endometrioides type, G1, n=35). We sought to analyze PPARs mRNA content as well as protein immunohistochemical expression that was further quantified by Western Blot technique. For both PPARα and PPARβ, protein expression was significantly higher in endometrial cancers compared to normal endometrial mucosa. In opposite, PPARγ protein expression was lower in endometrial cancer cells. In each case, immunohistochemical reaction was confined to the perinuclear and/or nuclear region. At the transcriptional level, the content of mRNA of all PPAR subunits did not follow the protein pattern of changes. These results provide evidence for altered PPAR's protein expression and disregulation of posttranslational processes in endometrial cancers.